IMPLEMENTASI PERATURAN DAERAH KOTA SEMARANG NOMOR 13 TAHUN 2011 TENTANG PAJAK BUMI DAN BANGUNAN DALAM MEWUJUDKAN DESENTRALISASI FISKAL - Isfariyanto, Noor Rahadjo, Henny Juliani (Program Studi S1 Ilmu Hukum, Fakultas Hukum, Universitas Diponegoro, 2012)
Economic development in the region is one of the goals of the government. Therefore, it required the efforts of the central government and local governments to increase budgetary revenue and expenditure. In order to realize the success of regional autonomy in accordance with Law No. 32 of 2004 jo Law Number 12 Year 2008 on Regional Government, the City of Semarang on demand capabilities in terms of providing funds for the administration and development of the sector especially in the area of local tax. In limpahkannya authority land and building tax (PBB) from the central government to the regions as an effort to increase revenue mainly from local taxation sector.The method used in this research is empirical juridical approach, the specification of descriptive analytical study, where the informants, the types and sources of data derived from field observations and literature study. What the research conducted at the Department of Finance and Asset Management District (DPKAD) of Semarang, the method of analysis, qualitative data analysis, verification or validation technique where the data were trigulasi.Land and Building Tax (PBB) as a very important local tax to be implemented in order to increase Revenue and Expenditure (Budget). For serious step that's needed for any local government to develop regional regulation as a basis for land and building tax collection. Preparation of Regulation on Land and Building Tax is a mandate of Law Number 28 Year 2009 on Regional Taxes and Levies, for land and building tax no later than December 31, 2013 the area had already made the Regulation on Land and Building Tax. Department of Finance and Asset Management District (DPKAD) Semarang as local agencies authorized to manage and administer local finance began in 2012 independently manages the Land and Building Tax (PBB), with the formation of Semarang Regional Regulation No. 11 Year 2011 on Land Tax and The building, in pewujudkan fiscal decentralization based on Law No. 32 of 2004 jo Law Number 12 Year 2008 on Regional Government.